Chemistry of low-valent early transition metals and lanthanides. - Minhas, Ravinder Iaur. (University of Ottawa (Canada), 1996)
Reactions of trans-TiCl$\rm\sb2(TMEDA)\sb2$ with two equivalents of RONa gave the paramagnetic linear trimeric (Ti$\rm\sb3(PhO)\sb9(TMEDA)\sb2\rbrack$ (2.1), dimeric (Ti(OR)Cl(TMEDA)) $\sb2(\mu$-OR)$\sb2$ (2.2) (R = 3,5-(t-Bu)$\rm\sb2C\sb6H\sb3\rbrack$ or monomeric (Ti(OR)$\rm\sb4\rbrack\lbrack Li(TMEDA)\sb2\rbrack$ (2.7) (R = 2,6-(iPr)$\rm\sb2C\sb6H\sb3$), indicating that the role of steric hindrance not only controls the geometry and the nuclearity of the complex, but also stabilizes the +3 oxidation state. Conversely, in the case of vanadium, it was possible to isolate and characterize monomeric and neutral V(II) aryloxides with a variety of coordination geometries like square-planar and saddle-shaped. Less bulky phenols give monomeric or dimeric products after disproportionation and oxidation. Similar to the case of titanium, vanadium aryloxides do not show any interaction with dinitrogen. Reaction of V ((2-OMe)C$\rm\sb6H\sb4O\rbrack\sb2$(TMEDA) (4.7) with Me$\rm\sb3SiCHN\sb2$ gave $\{$ ((2-OMe)C$\rm\sb6H\sb4O\rbrack\sb2V\}\sb2 \lbrack\mu$-NNCHSiMe$\sb3\rbrack\sb2$ co-crystallized with $\{$ ((2-OMe)C$\rm\sb6H\sb4O\rbrack\sb2V\}\sb2 \lbrack\mu$-(2-OMe)$\rm C\sb6H\sb4O\rbrack\sb2$ (4.14). The structures of these complexes were determined by X-ray analysis. The synthesis and reactions of ionic Ti(III) amides with RLi are discussed. Sterically demanding alkyl groups (R = CM$\rm\sb2CMe\sb3,\ CH\sb2SiMe\sb3,\ CH\sb2CMe\sb2Ph\rbrack$ led to disproportionation and isolation of Ti(IV) complexes of the formulation ((Cy$\rm\sb2N)\sb2TiR\sb2\rbrack$ whereas with MeLi & BzLi, (Cy$\rm\sb2N)\sb2TiR\sb2$Li(TMEDA) (R = Bz (3.4a), Me (3.4b)) was formed, thus retaining the +3 oxidation state of titanium. Thermolysis of (Cy$\rm\sb2N)\sb2TiNf\sb2$ gave (Cy$\rm\sb2N)\sb2TiCH\sb2C(Me)\sb2C\sb6H\sb4$ (3.10) after losing a molecule of neophane. The ability of three-center chelating ligands (such as formamidinates or benzamidinates) to form dinuclear complexes with a short M-M contact was studied in order to understand the role of bridging ligands in promoting or disfavoring the dinuclear aggregation and to determine the extent of intermetallic separation in such species. The reaction of Li amidinates with trans-VCl$\rm\sb2(TMEDA)\sb2$ gave dinuclear ((CyNC(H)NCy)$\rm\sb2V\rbrack\sb2$ (5.3), monomeric (CyNC(Me)NCy) $\rm\sb2V(THF)\sb2$ (5.7) and (Me$\rm\sb3SiNC(Ph)NSiMe\sb3\rbrack\sb2V(THF)\sb2$ resulted in the formation of V(III) complex (CyNC(Me)NCy) $\sb3$V (5.6) whereas in the case of (Me$\sb3$SiNC(Ph)NSiMe$\sb3\rbrack\sb2$V(THF)$\sb2$ a novel dinitrogen complex ($\{\rm Me\sb3SiNC(Ph)NSiMe\sb3\}\sb2V\rbrack\sb2(N\sb2)$ (5.12) was formed. All these complexes could also be synthesized via reduction of V(III) amidinates. Reactions of LiNR$\sb2$ with SmCl$\sb3$(THF)$\sb3$ in a 2:1 molar ratio gave Sm(III) amides with different formulations and structures depending upon the R group of the amide. Dimeric ((Cy$\rm\sb2N)\sb2Sm(THF)(\mu$-Cl)) $\sb2$ (6.1) was obtained from the reaction of SmCl$\sb3$(THF)$\sb3$ with Cy$\sb2$NLi whereas ((i-Pr$\sb2\rm N)\sb2SmCl\sb3(LiTMEDA)\sb2$) (6.2) was obtained from the amide, iPr$\sb2$NLi under similar reaction conditions but in the presence of TMEDA. The reactivity of these amides was studied which gave another variety of Sm(II) amides like ((Cy$\rm\sb2N)\sb6Sm\sb4Cl\sb6(THF)\sb2$) (6.3) and ((Cy$\rm\sb2N)\sb4$SmLi(THF)) (6.4). Attempts to reduce (6.1) gave either metallic samarium or Sm(Cy$\rm\sb2N)\sb3$(THF) (6.5). The direct synthesis of a Sm(II) amide was possible only with Ph$\sb2$N, the salt having no $\alpha$-hydrogen. Using Ph$\sb2$N as the ligand, both ionic (Sm(Ph$\rm\sb2N)\sb4Na\sb2(TMEDA)\sb2$) (6.6) and neutral (Sm(Ph$\rm\sb2N)\sb2(THF)\sb4\rbrack$ (6.7) complexes were obtained. The structures of all these complexes are demonstrated by X-ray analysis.
Keywords: Chemistry, Inorganic.